ANALISIS RISK DAN RETURN SAHAM SYARIAH TAHUN 2016 - Angga Binanga; Muhammad Dayyan; Ainun Mardhiah (Jurnal Investasi Islam, 2017)
This study was conducted to see whether the ISSI investment instrument which is sharia stock has or has not different risk and return with non-ISSI as conventional stock. ISSI and Non-ISSI shares in this study equally amounted to 267 issuers with a total of all 547 issuers. Differences risk and stock returns were analyzed using secondary data downloaded through the yahoo finance website. The data used are the opening and closing prices of daily trading, as well as cash dividends distributed by issuers from January 4 to December 30, 2016. The Kolmogorov-Smirnov and Shapiro-Wilk normality tests are used to determine whether different tests will use parametric statistics (Independent T Test) or nonparametric (Mann-Whitney). Normality test results show that the significance value of risk and return of ISSI and Non-ISSI stock is smaller than tolerance of 0.05 so that the difference test is done using Mann-Whitney nonparametric statistics. Mann-Whitney test results show Asymp. Sig. (2-tailed) return value of 0.238 and Asymp. Sig. (2-tailed) risk is worth 0.812. Both values of significance are greater than 0.05 which means that Ho in this study is accepted, “there is no significant difference in risk and return between ISSI sharia shares and non-ISSI conventional shares.